2015
DOI: 10.17219/acem/29184
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endovascular Aneurysm Repair with Open Repair in Patients with Abdominal Aortic Aneurysm in Our Own Material in Years 2002-2011

Abstract: Background. Endovascular abdominal aortic aneurysm repair has become an alternative to open surgical repair of abdominal aortic aneurysm since the early 1990s. The conventional method remains the gold standard in the treatment of Abdominal Aortic Aneurysm (AAA); however, a large percentage of patients do not qualify for this treatment due to the high risk of perioperational death and complications. Objectives. The objective of this work was to compare AAA surgeries performed by both classical and endovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…World studies on AAA patients treated during elective admissions using the endovascular method show short-term mortality rates of 0 to 4.3% [1,5,7,13,15,[18][19][20][21][22][23][24][25][26][27][28][29][30]. The short-term mortality of 2.5% characterized the patients with elective endovascular treatment in the present study and is comparable to cited reports.…”
Section: Mortalitysupporting
confidence: 85%
See 1 more Smart Citation
“…World studies on AAA patients treated during elective admissions using the endovascular method show short-term mortality rates of 0 to 4.3% [1,5,7,13,15,[18][19][20][21][22][23][24][25][26][27][28][29][30]. The short-term mortality of 2.5% characterized the patients with elective endovascular treatment in the present study and is comparable to cited reports.…”
Section: Mortalitysupporting
confidence: 85%
“…The present study analyses the treatment outcomes for 236 AAA patients subject to planned endovascular surgery between 2010 and 2015. The patients with AAA treated in the elective endovascular method demonstrated a low short-term mortality rate, which is no different from worldwide reports on the use of the endovascular technique [1,5,7,13,15,[18][19][20][21][22][23][24][25][26][27][28][29][30]. Furthermore, in this study the observed and predicted short-term mortality rates according to the V-Possum scale were not significantly different (p = 0.7993).…”
Section: Discussioncontrasting
confidence: 61%
“…Due to the low invasiveness, less trauma and perioperative pain, as well as shorter hospitalization time and faster return to full fitness, the endovascular technique is becoming the preferred treatment for AAA patients worldwide [ 1 7 ]. In a UK study, AAA patients undergoing planned endovascular treatment were found to have low rates of short-term mortality and complications – 0% and 12%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low invasiveness of the endovascular method allows the procedure to be performed under local anesthesia, with less trauma and less perioperative pain. The potential benefits of the endovascular method also include shorter hospitalization and a reduction in the rates of perioperative complications and mortality [ 3 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In high-risk patients (n = 275) with infra-renal AAA, EVAR has been shown in a retrospective study to have significantly lower mortality at 30 days and 1 year compared with open repair [32]. Utilization of EVAR for ruptured AAA is also expanding.…”
Section: High-risk Patients and Ruptured Aaamentioning
confidence: 99%